2003
DOI: 10.1046/j.1442-9071.2003.00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Limited macular translocation for subfoveal choroidal neovascularization in age‐related macular degeneration

Abstract: In this small case series, limited macular translocation was found to be an effective and reproducible means of treating small well-defined subfoveal CNV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Chang et al reported that the mean BCVA improved by 0.19 logMAR units at 1 year after the LMT surgery. [20] These findings are in good agreement with our results in which the postoperative vision improved by 2 or more lines in 45%, and the mean improvement in BCVA was by 0.24 logMAR at 1 year after the surgery. These results indicate that the impaired function of the sensory retina of the fovea can recover when the retina is translocated onto healthy RPE.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Chang et al reported that the mean BCVA improved by 0.19 logMAR units at 1 year after the LMT surgery. [20] These findings are in good agreement with our results in which the postoperative vision improved by 2 or more lines in 45%, and the mean improvement in BCVA was by 0.24 logMAR at 1 year after the surgery. These results indicate that the impaired function of the sensory retina of the fovea can recover when the retina is translocated onto healthy RPE.…”
Section: Discussionsupporting
confidence: 91%
“…[17] Although many studies have reported favorable outcomes, the longest follow-up period has been 2 years after the LMT. [1420] The long-term results of LMT should provide important evidence on whether an impaired sensory retina can recover after it is moved onto healthy RPE, and the good visual function can be maintained for a longer period. A search of Medline did not extract any publications describing the outcomes of LMT after 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…Scleral shortening is achieved by either scleral resection or imbrication, obviating the need for large retinotomies that should reduce the incidence of PVR. LMT only allows a limited translocation distance of 1100–1300 µm 47,48 and the high rate of recurrence casts doubts on its validity 49 . The SST reports have shown that surgically excised subfoveal neovascular lesions from AMD patients measure between 1800 and 1980 µm 50 .…”
Section: Surgical Treatment Of Amdmentioning
confidence: 99%